Analisis Penerimaan Core Banking System Berbasis Technology Readiness an Acceptance Model pada BPRS Bangun Drajat Warga di DIY - Sindu Rifai; Salamatun Asakdiyah; Rai Rake Setyawan (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to analyze the acceptance of the core banking system based on technology readiness and acceptance model on Bank Pembiayaan Rakyat Syariah Bangun Drajat Warga in the Special Region of Yogyakarta. Constructions used are optimism, innovativeness, discomfort, insecurity, easy of use and usefulness. This research method uses quantitative with a survey approach. The results of the study show that constructs of optimism and discomfort have a positive and significant effect on the perception of benefits and convenience in using the Core Banking System. The innovativeness construct has a positive and significant effect on the perception of the benefits of the core banking system, but for users, it has a negative effect and does not significantly influence the perception of ease of use of the Core Banking System. Insecurity, easy of use and usefulness constructs shows that there is no positive and significant influence on the perception of benefits and convenience in using the Core Banking System.